Quantum cosmology, possible worlds, and modal actualism - Życiński, Joseph (Theoria et Historia Scientiarum, 2007)
The growth of modern science resulted in a radically new cognitive approach to many problems of classical philosophy. In the context of contemporary theoretical physics, if only one avoids easy apologetic, it is no longer possible to defend this version of epistemological empiricism that was defended half a century ago. Whereas in the 1930’s the traditional distinction between theoretical and observational terms was called into question, due to its arbitrary nature, in the 1980’s the basic philosophical opposition between material and immaterial (resp. between physical and mathematical) objects seems arbitrary since the very notion of matter appears nothing but a terminological relic of the bygone epoch.